Sweet potato soul : 100 easy vegan recipes for the southern flavors of smoke, sugar, spice, and soul - Claiborne, Jenne (New York : Harmony Books, 2018)
A collection of soul food and Southern cooking plant-based recipes from the vegan personal chef and popular blogger features such dishes as sweet potato pancakes, miso peachy arugula salad, Cajun blackened tofu sandwich, and strawberry shortcake.
Claiborne shares soul food and Southern cooking plant-based recipes. She explores the history behind some of the recipes, as well as their innate health benefits. If you've wondered how one can make dandelion, mustard, and turnip greens into nutrition superstars, this is your chance to see how Claiborne infuses these plants with the flavors and the depth that feed the soul.
Breakfast -- Salads & soups -- Greens & sides -- Mains -- Sweets & drinks -- Pantry staples & sauces.
Includes index.
109399
Keywords: Vegan cooking; African American cooking; Cooking -- Regional & Ethnic -- Soul Food; Cooking -- Vegetarian; Cookbooks